Aerial spraying for downy mildew control in grapevines using a remotely piloted aircraft (Acta Scientiarum. Agronomy, 2024)
Downy mildew is a major problem for grape growers, as this disease is difficult to control. Synthetic fungicides are used to treat downy mildew with handheld backpack and tractor sprayer applications, with high chemical exposure by operators. As important tools for maximising yield, application technologies must be studied to optimise control efficiency. The objective of this study was to evaluate the efficiency of fungicide spray application using Remotely Piloted Aircraft (RPA) for the control of downy mildew in grapevine, with different spray volumes. The study was divided into two experiments using 4 vine lines, 10 blocks and 5 treatments with different mixture volumes: Experiment 1 with RPA application of 5 mixture volumes - 0, 22, 44, 66, and 88 L ha−1; Experiment 2 with RPA application of 3 mixture volumes - 44, 66, and 88 L ha−1 and a backpack application of one mixture volume - 800 L ha−1. Coverage percentage, droplet density and volume median diameter (VMD) were evaluated. Downy mildew severity on grapevine leaves was assessed using visual analysis and a diagrammatic scale. The application of 44 L ha−1 provided the greatest coverage and droplet density in the upper and middle strata; however, the backpack application had a better droplet distribution than the RPA application. Treatments of 44 L ha−1 with RPA and backpack application (800 L ha−1) provided the best disease control. In the trellis system, RPA application must be improved because of the low coverage in the lower parts of the plant, and further studies with different spray nozzles and application heights are needed.